Judo for older adults: the coaches' knowledge and needs of education - Ciaccioni, Simone; Guidotti, Flavia; Palumbo, Federico; Forte, Roberta; Galea, Envic; Sacripanti, Attilio; Lampe, Nuša; Lampe, Špela; Jelušić, Toma; Bradić, Slaviŝa; Lascau, Maria-Loredana; Rodica-Borza, Alina; et al. (Frontiers in Sports and Active Living, 2024)
This study aimed to explore the views of judo coaches on their perceived knowledge (PK) and needs for education (NE) for training older practitioners. In total, 470 international (Europe=48%, Americas=22%, Africa=23%, Asia=5% and Oceania=2%) judo coaches (IJF: level 1=55,3%, level 2=33%; judo black belt: 3,4±1,7 dan; F=15%; university education: 68% >BA) responded an online survey encompassing demographic information and 35 items relevant to training older adults (Aging process; Safety and First Aid; Organization & Environment; Physiology and Fitness; Psychology & Mental Health; Teaching & Training) to be rated on a 7-point Likert scale for PK and NE. Non parametric statistics (p>0.05) was applied to ascertain differences and relationships between PK and NE, respectively. A bivariate go-zone plot was used to highlight items with the lowest PK and the highest NE mean values. The coaches reported high PK (4.5±0.3 pt) and NE (4.7±0.1 pt) values, with significant higher PK values emerging for high education levels and judo experience. In considering their unique needs and special role, the judo coaches presented valuable insights to develop a sustainable educational curriculum tailored to train older judo practitioners.